Integrated Positron Emission Tomography/Magnetic Resonance Imaging for Resting-State Functional and Metabolic Imaging in Human Brain: What Is Correlated and What Is Impacted - Shan, Yi; Wang, Zhe; Song, Shuangshuang; Xue, Qiaoyi; Ge, Qi; Yang, Hongwei; Cui, Bixiao; Zhang, Miao; Zhou, Yun; Lu, Jie (Frontiers in Neuroscience, 2022)
Integrated PET/MR could simultaneously obtain both functional MRI (fMRI) and 18F-fluorodeoxyglucose (FDG) PET thus provide multiparametric information for analysis of brain metabolism. In this study, we aimed to, for the first time, investigate the interplay of simultaneous fMRI and FDG PET scan using a randomized self-control protocol. 24 healthy volunteers underwent PET/MR scan 30 to 40 minutes after the injection of FDG. A 22-minute brain scan was separated into MRI-off (without fMRI pulsing) and MRI-on modes (with fMRI pulsing) with each one lasting for 11 minutes. We calculated the voxel-wise fMRI metric (regional homogeneity (ReHo), amplitude of low frequency fluctuations (ALFF), fractional amplitude of low frequency fluctuations (fALFF) and degree centrality (DC)), resting networks, relative standardized uptake value ratios (SUVr), SUVr slope and regional cerebral metabolic rate of glucose (rCMRGlu) maps. Paired two-sample t-tests were applied to assess the statistical differences between SUVr, SUVr slope, correlation coefficients of fMRI metrics and rCMRGlu between MRI-off and MRI-on mode, respectively. Voxel-wise whole brain SUVr revealed no statistical difference, while SUVr slope was significantly elevated in sensorimotor, dorsal attention, ventral attention, control, default and auditory networks (P＜0.05) during fMRI scan. Task-based group ICA revealed that the most active network components derived from combined MRI-off and MRI-on static PET images were frontal pole, superior frontal gyrus, middle temporal gyrus and occipital pole. High correlation coefficients were found among fMRI metrics with rCMRGlu in both MRI-off and MRI-on mode (P＜0.05). Our results systematically evaluated the impact of simultaneous fMRI scan on quantification of human brain metabolism from an integrated PET/MR system.